Aesthetic ideology - De Man, Paul (Theory and history of literature ;, 1996)
Offers the definitive resource to de Man's thoughts on philosophy, politics, and history. The texts collected here were written or delivered as lectures during the last years of de Man's life, between 1977 and 1983. Many of them have never been available previously in any form.